G2-S16 dendrimer as a candidate for a microbicide to prevent HIV-1 infection in women. Issue 27 (4th July 2017) - Ceña-Diez, Rafael; García-Broncano, Pilar; Javier de la Mata, Francisco; Gómez, Rafael; Resino, Salvador; Muñoz-Fernández, Mª Ángeles
Abstract : Unprotected heterosexual intercourse is the first route for sustaining the global spread of human immunodeficiency virus type 1 (HIV-1), being responsible for 80% of new HIV-1 infections in the world. Abstract : Unprotected heterosexual intercourse is the first route for sustaining the global spread of human immunodeficiency virus type 1 (HIV-1), being responsible for 80% of new HIV-1 infections in the world. The presence of inflammation in the female reproductive tract and the presence of semen increases the risk of heterosexual HIV-1 transmission. This state-of-the-art research based on an innovative nanotechnology design was focused on a toxicological study of the limitation of the activity of the novel H2 O-soluble anionic carbosilane dendrimer G2-S16 in the adult cervical and foreskin epithelia. The G2-S16 dendrimer did not cause any irritation or inflammation in the vaginal epithelium, proving that this dendrimer is a safe nanocompound for vaginal application to control viral transmission. It was shown that no significant differences were found in mortality, sublethal or teratogenic effects when the zebra fish embryos were treated with G2-S16. In short, G2-S16 seems to be an ideal candidate for the development of a topical microbicide against HIV-1 infection and the next step is try in clinical trials, because of its great in vivo biocompatibility, as well as its ability to halt HIV-1 infection in the presence of semen.